2014
DOI: 10.1016/j.bjid.2013.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Extended spectrum β-lactamase producers among nosocomial Enterobacteriaceae in Latin America

Abstract: To review the epidemiology of nosocomial extended spectrum β-lactamase-producing Enterobacteriaceae in Latin America, a systematic search of the biomedical literature (PubMed) was performed for articles published since 2005. Rates of nosocomial infections caused by extended spectrum β-lactamase-producing Enterobacteriaceae in Latin America have increased since 2005. Up to 32% of Escherichia coli and up to 58% of Klebsiella pneumoniae isolates are extended spectrum β-lactamase-positive, rates that are higher th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
3
14

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(62 citation statements)
references
References 67 publications
3
41
3
14
Order By: Relevance
“…High frequencies of ESBL-producing Enterobacteriaceae have been reported in Latin America by previous surveillance studies, particularly K. pneumoniae and E. coli [2]. In this update we have shown the rate of these organisms to be 36.3% and 25.4%.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…High frequencies of ESBL-producing Enterobacteriaceae have been reported in Latin America by previous surveillance studies, particularly K. pneumoniae and E. coli [2]. In this update we have shown the rate of these organisms to be 36.3% and 25.4%.…”
Section: Discussionsupporting
confidence: 54%
“…Sader et al [18] reported higher rates of ESBL-producing K. pneumoniae and E. coli (57.3 and 37.7%, respectively) from the SENTRY study of Latin American centers (2011–2014). Differences could be in part due to the different countries included in each study, and variable rates of ESBL production across Latin America have previously been reported [2]. Furthermore, the rates of ESBL production in this T.E.S.T.…”
Section: Discussionmentioning
confidence: 90%
“…Otros antibióticos, como la colistina y la tigeciclina, se utilizan para el tratamiento contra microorganismos portadores de carbapenemasas (20,21), y nuestros aislamientos presentaron sensibilidad in vitro frente a estos dos agentes. Sin embargo, actualmente ya hay reportes de aislamientos portadores de KPC resistentes a estos antibióticos en Estados Unidos (22), Europa (23,24) Asia (25) y, más recientemente, en Suramérica (26).…”
Section: Resultsunclassified
“…Species producing extended spectrum β-lactamases (ESBL), have been frequently observed, among them Klebsiella pneumoniae and Escherichia coli (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%